Toxic Epidermal Necrolysis-Like Lesions and Systemic Lupus Erythematosus Possibly Triggered by Sulfasalazine - Krabbe, Simon (Case Rep Rheumatol, 2016)
This case report describes a patient with arthritis of the large joints, bilateral sacroiliitis, and positive anti-SSA and anti-dsDNA antibody, who received sulfasalazine and shortly thereafter became critically ill. He developed toxic epidermal necrolysis, hemolytic anemia, lymphopenia, markedly elevated ferritin, and muscle wasting. A diagnosis of systemic lupus erythematosus was made, and mycophenolate mofetil and systemic glucocorticoids brought this severe disease under control. Toxic epidermal necrolysis-like lesions and hemophagocytic syndrome have been reported as manifestations of systemic lupus erythematosus. This patient possibly had spondyloarthritis or an undifferentiated connective tissue disease at presentation, and we suggest, based on the timing of events, that sulfasalazine may have acted as a trigger of the severe disease manifestations.